Dynamic changes occur in the cell wall composition and related enzyme activities during flower development in Rosa damascena - Önder, Sercan; Tonguç, Muhammet; Önder, Damla; Erbaş, Sabri; Mutlucan, Murat (Frontiers in Plant Science, 2023)
The flowering period of oil-bearing rose is short and many changes occur in the cell wall during blooming. Changes in the cell wall composition and associated enzyme activities are important as they allow cells to divide, differentiate and grow. In the present study, changes in 7 cell wall components and 6 cell wall related enzyme activities at five flower development stages were investigated and the relationship between these parameters and flowering were examined. Neutral detergent fiber (NDF), acid detergent fiber (ADF) and hemicellulose contents increased after the stage I, but did not change significantly at the other developmental periods. Ash content did not change between stages I to III, but decreased after stage IV of flower development. Pectin content increased throughout the flower development. An "increase-decrease" trend was observed in total cellulose content and a "decrease-increase" pattern in uronic acid content. The activities of glucosidase enzymes, (β-galactosidase, β-glucosidase and endoglucanase) and the activities of pectin hydrolase enzymes (pectin lyase, pectin methyl esterase and polygalacturonase) increased till the stage IV and their activities decreased significantly at the stage V of flower development. Correlation analysis revealed a 14 positive and one negative correlation with the studied parameters. Pectin content was positively and cellulose content was negatively correlated with all cell wall related enzymes. Cell wall glucosidase enzymes showed a positive and significant correlation with pectin hydrolysis enzymes. Principal component analysis (PCA) showed that ADF, NDF and cellulose content were significantly changed at stage II of flower development, and all cell wall enzyme activities were significantly increased at stage IV. Overall, blooming is correlated closely with increased pectin, decreased cellulose contents, and changes in cell wall glucosidase and pectin hydrolysis enzyme activities. These results show that cell wall modifying enzymes are part of flower development process in oil-bearing rose.